PENGEMBANGAN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF MENGGUNAKAN ADOBE FLASH CS3 PADA MATAKULIAH MEDIA PEMBELAJARAN EKONOMI YANG MENERAPKAN METODE PROJECT BASED LEARNING - Dewi, Ika Parma; Sofya, Rani; Sriwahyuni, Titi (Jurnal Teknologi Informasi dan Pendidikan, 2018)
This study aims to produce, analyze validation tests, practicalities and effectiveness of interactive multimedia Using Adobe Flash CS3 for Economics Learning Media Courses that Implement Project Based Learning Methods. This research uses research and development (R & D) methods. The module development model uses the IDI (Instructional Development Institute) model, the principles of the system approach which include three stages, namely define, develop, and evaluate. This interactive multimedia in the form of learning media that has been valid can help students to better understand and improve the subjects of economic learning media that apply the Project Based Learning Method. Effectiveness Test of interactive multimedia economic learning media courses that use the project Based Learning method as a supporting media for independent learning states that interactive multimedia is effective, this is evidenced by the improvement in student learning outcomes.